PENERAPAN MODEL PENGEMBANGAN KURIKULUM SYSTEMATIC ACTION RESEARCH DI PESANTREN TAHFIDZ MASKANUL HUFFADZ - Zul fitria; Zainal arif; Ayu Lestari (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
ABSTACTThis study aims to see how the development of a systemic action research curriculum model that can be applied at the Tahfidz Maskanul Huffadz Islamic Boarding School looks like. The Tahfidz Islamic Boarding School as a religious education institution that focuses on the Koran, where there is no standard curriculum that must be applied, so it requires the application systematic action research curriculum development model, so that the curriculum applied is in accordance with the needs and desires. zThe zstudy zused za zqualitative zapproach zto zobtain zan zin-depth zdescription zof zthe zproblems zthat zoccurred zby zusing zdata zcollection zin zthe zform zof zobservations, zinterviews zand zdocumentation. zThe zresearch zwas zconducted zat zthe zTahfidz zMaskanul zHuffadz zIslamic zBoarding zSchool zlocated zin zPondok zAren zBintaro, zSouth zTangerang. zFrom zthe zresults zof zthis zstudy, zwe zcan zsee zthe zeffectiveness zof zthe zimplementation zof zthis zcurriculum zwhich zin zits zapplication zis zvery zdynamic zand zcan zbe zadapted zto zthe zneeds zof zthe zimplementation zof zIslamic zboarding zschool zeducation.